Запишем тригонометрическое тождество.
Поделим выражение на cosa получим
Откуда tga
tga=
Откуда получим следующее
Объяснение:
Запишем тригонометрическое тождество.
Поделим выражение на cosa получим
Откуда tga
tga=![\sqrt{\frac{1}{cosa^{2} }-1 }](/tpl/images/1080/3811/1ab6b.png)
tga=![\sqrt{\frac{1}{(-\frac{12}{13}) ^{2} }-1 }](/tpl/images/1080/3811/2d424.png)
Откуда получим следующее
tga=![\sqrt{\frac{169}{144} -1}](/tpl/images/1080/3811/bc772.png)
tga=![\sqrt{\frac{169}{144} -\frac{144}{144} } \\](/tpl/images/1080/3811/589d0.png)
tga=![\sqrt{\frac{25}{144} } \\](/tpl/images/1080/3811/e00c1.png)
tga=![\frac{5}{12}](/tpl/images/1080/3811/3f78e.png)
Объяснение: